2011
DOI: 10.1007/s10518-011-9291-1
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of energy damping in unreinforced masonry rocking mechanisms. Experimental and analytic investigations

Abstract: Existing unreinforced masonry buildings frequently suffer out-of-plane local collapse mechanisms when undergoing earthquake ground motion. The energy damping that occurs during the motion, due to impacts of a wall against the foundation or against other walls, is a relevant parameter on the response. An experimental investigation has been carried out to estimate the dissipation of kinetic energy that takes place during free oscillations. Restraint conditions allow for two-sided rocking (wall resting on a found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(123 citation statements)
references
References 23 publications
6
117
0
Order By: Relevance
“…A common approach, relying on the classical hypothesis of the impulse dynamics, is simulating the energy dissipation involved in such mechanisms through a coefficient of restitution [4][5]20]. Another option is adopting an equivalent viscous damping approach defining a velocity dependent damping force through a constant, variable (with cycleto-cycle iterations) and stiffness proportional damping ratio.…”
Section: Energy Dissipation In Rocking Structuresmentioning
confidence: 99%
“…A common approach, relying on the classical hypothesis of the impulse dynamics, is simulating the energy dissipation involved in such mechanisms through a coefficient of restitution [4][5]20]. Another option is adopting an equivalent viscous damping approach defining a velocity dependent damping force through a constant, variable (with cycleto-cycle iterations) and stiffness proportional damping ratio.…”
Section: Energy Dissipation In Rocking Structuresmentioning
confidence: 99%
“…Indeed, the body not being fully rigid, the moment of momentum was not conserved. In this line, also Sorrentino et al [22] carried out an experimental campaign on URM solid clay brick or tuff specimens for two-sided and one-sided motion, with height to thickness ratios varying between 6.5 and 14.6. The authors found values of the restitution coefficient equal to 95% of the theoretical value.…”
Section: Geometry Influence and The Formulation Of Energy Dissipationmentioning
confidence: 99%
“…In [20], a probabilistic approach was suggested to solve this issue. As concerns sliding, the absence of it is acceptable when the static coefficient of friction is larger than the ratio b/h [22,28]. Generally, masonry walls have this ratio much lower than the static friction coefficient, usually equal to 0.6-0.7 [28].…”
Section: Bouncing: Sliding Phenomena and The Role Of Vertical Ground mentioning
confidence: 99%
“…This impact obviously dissipates energy. The approach proposed by Housner to account for the dissipation is to consider the conservation of angular momentum with various assumptions (see [7]). According to this, a reduction factor e is defined and has to be applied to the velocity of the wall before the impact to obtain the velocity right after this impact.…”
Section: Coefficient Of Restitutionmentioning
confidence: 99%
“…The formulation of the restitution coefficient used in the basic reference model is the one proposed by [7] deduced from the theory developed by Housner. An alternative formulation is however proposed by [8], also on the base of the Housner theory, that can in the present case be further simplified according to the specific expression of I O :…”
Section: Restitution Coefficientmentioning
confidence: 99%